OBSERVATION ON THE URINOGENITAL PAPILLA AND SEXUAL DIMORPHISM IN SOME INDIAN GOBIIDS (GOBIIDAE: TELEOSTEI) - HAR, SAKTI P (Journal of Indian Fisheries Association, 2015)
A thorough comparative study on the urinogenital papilla and sexual dimorphism has been made for the first time in both the sexes of twelve Indian gobiids- Glassogobius giuris (Han1ilton); Acentrogobius cyanomos (Bleeker); Eleotriodes muralis (Valenciennes); Parapocryptes serperaster (Richardson); Apocryptes bato (Hamilton); Scartclaos viridis (Hamilton); Boleophthalmus boddarti (Pallas), Periophthalmus schlosseri (Pallas); P. koelreuteri (Pallas); Taenioides anguillaris (Linnaeus); T. buchanani (Day); Odontamblyopus rubicundus (Hamilton). The urinogenital papilla, originating as a free muscular organ from the ventral surface of the body-wall and shortly behind anus, is present in both the sexes. It is an important organ of primary sex recognition in all species. In case of male the papilla is conical, broad at the base and in female it is either flattened, distally truncated or bluntly rounded. The presence of permanent colour mark over the specific region of the body surface is another secondary sexual character in a few species. Besides, colouration may also be a nuptial secondary sex character developed in some during peak breeding season. The enlargement and colouration of the organ is subject to seasonal variations parallel to the seasonal gonadal cycle. The histological architecture of the papilla shows a high degree of cellular specialization and an interrelationship to the urinary and genital ducts. The functional efficacy and significance of the papilla in the breeding biology of these fishes has been discussed. Keywords : Gobiidae, Sexual dimorphism, Urinogenital papilla